2014
DOI: 10.4081/ijfs.2014.4143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carcass hygiene in sheep subjected to gas de-pelting with different skinning procedures

Abstract: The aim of the study was to evaluate the hygienic status of sheep carcasses skinned with two different procedures, the pulling down and Y cut methods, with and without the use of compressed filtered air inflation. Five sheep carcasses per day for each of the four skinning methods considered were sampled on ten different slaughtering days using wet and dry swab techniques at a local abattoir specialised in ovine slaughtering. A pool of four different sampling sites (brisket, shoulder, thorax and rump) was consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Furthermore, the ACC and ENT levels are in line with those reported for "farmed" animals (bovine and swine) [34,35] and values suggested as acceptable by EU legislation criteria for hygiene processes (acceptable levels in swine between 4.0 and 5.0 log CFU/cm 2 for ACC and between 2.0 and 3.0 log CFU/cm 2 for ENT) [34]. Indeed, 6 and 12 samples out of 120 sampled carcasses (7.2% and 14.4% prevalence) exceeded the acceptable level set by EU legislation for ACC and ENT respectively [36].…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the ACC and ENT levels are in line with those reported for "farmed" animals (bovine and swine) [34,35] and values suggested as acceptable by EU legislation criteria for hygiene processes (acceptable levels in swine between 4.0 and 5.0 log CFU/cm 2 for ACC and between 2.0 and 3.0 log CFU/cm 2 for ENT) [34]. Indeed, 6 and 12 samples out of 120 sampled carcasses (7.2% and 14.4% prevalence) exceeded the acceptable level set by EU legislation for ACC and ENT respectively [36].…”
Section: Discussionsupporting
confidence: 86%
“…Despite these criteria, which are implemented to evaluate the slaughtering hygiene during a period of time and pools of different carcasses during the same day taken into consideration in the EC Regulation [ 11 ], these findings confirm that the procedures adopted during hunting on the carcasses, if properly and hygienically implemented, could be as hygienic as at the slaughterhouse level [ 19 , 25 , 26 ]. Furthermore, the results registered are close to those of slaughtered animals, such as ovine [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, there was less fecal contamination risk during evisceration due to the natural pellet form of sheep feces, which does not stick and smear to the carcass. Previous studies have indicated the absence (Kuma et al, 2017;Ranucci et al, 2014) or presence (Duffy et al, 2010;Stipetic et al, 2016;Tekelu and Negussie, 2011) of Salmonella in sheep carcasses. Differences observed in prevalence rates in these studies were reported to arise from the general hygiene status of slaughterhouses; whether slaughtering is applied in monorail conveyors or on the floor; sheep's initial pathogen carriage rate, increasing risk of shedding during transport stress leading to higher fecal contamination of carcass, and differences in sensitivity of Salmonella detection procedures.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, the Turkish Food Codex (TFC) Regulation on Microbiological Criteria (TFC, 2011) has zero tolerance for the detection of Salmonella from ovine carcasses assessed with EN/ISO 6579 (ISO, 2002) as the reference method. Accordingly, several studies have reported Salmonella prevalence in sheep carcasses (0%-26.7%) (Kuma et al, 2017;Ranucci et al, 2014;Stipetic et al, 2016), in fecal samples (0%-26.90%) (Dargatz et al, 2015;Hanlon et al, 2018;McAuley et al, 2014), in edible organs such as liver (0.9%-4.3%) and spleen (0%-2.27%) (Kuma et al, 2017;Molla et al, 2006;Woldemariam et al, 2005), in gallbladder (3%) (Zubair and Ibrahim, 2012) and in mesenteric lymph nodes (3.85%-13.6%) (Hanlon et al, 2018;Kuma et al, 2017;Tadesse and Tessema, 2014), where S. Typhimurium was reported as the predominant serovar regardless of the sample type.…”
Section: Articlementioning
confidence: 99%